Pemberdayaan Masyarakat Melalui Pengelolaan Sampah di Kelurahan Purwokerto Wetan - Muslim Fikri; Ida Nurlaeli (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The waste problem, especially in the Purwokerto Wetan area, is an urgent problem that needs to be resolved immediately. With population growth and increasing consumption behavior, the amount of waste continues to increase. Garbage problem is a common problem. To overcome this, unity and unity are needed. The government has all the limitations and possibilities and cannot work alone. All citizens need to raise awareness of waste management and campaign on a large scale and consistently. The research was conducted from July to August at the 3R Integrated Waste Management Installation (TPST) in Purwokerto Wetan Village and the Community Self-Help Team (KSM) “SAE”. The methods used to carry out these activities are observation and interviews, program development, field processing, waste sorting, as well as socialization and public education in waste management. The results and conclusions of this activity are that the waste generated in the area has been disposed of properly and residents are aware of the importance of a clean and healthy lifestyle.